Tissue Hydrogen Peroxide Concentration Can Explain the Invasiveness of Aquatic Macrophytes: A Modeling Perspective - Asaeda, Takashi; Rashid, Md Harun; Schoelynck, Jonas (Frontiers in Environmental Science, 2021)
In recent years, an invasive macrophyte, Egeria densa, has overwhelmingly colonized some midstream reaches of Japanese rivers. This study was designed to determine how E. densa has been able to colonize these areas and to assess the environmental conditions that limit or even prevent colonization. Invasive species (E. densa and Elodea nuttallii), and Japanese native species (Myriophyllum spicatum, Ceratophyllum demersum, and Potamogeton crispuss) were kept in experimental tanks and a flume with different environmental conditions. Tissue hydrogen peroxide (H2O2) concentrations were measured responding to either individual or multiple environmental factors of light intensity, water temperature, and water flow velocity. In addition, plants were sampled in rivers across Japan, and environmental conditions were measured. The H2O2 concentration increased in parallel to the increment of unpreferable levels of each abiotic factor, and the trend was independent of other factors. The total H2O2 concentration is provided by the sum of contribution of each factor. Under increased total H2O2 concentration, plants first started to decrease in chlorophyll concentration, then reduce their growth rate, and subsequently reduce their biomass. The H2O2 concentration threshold, beyond which degradation is initiated, was between 15 and 20 µmol/gFW regardless of the environmental factors. These results highlight the potential efficacy of total H2O2 concentration as a proxy for the overall environmental condition. In Japanese rivers, major environmental factors limiting macrophyte colonization were identified as water temperature, high solar radiation, and flow velocity. The relationship between the unpreferable levels of these factors and H2O2 concentration was empirically obtained for these species. Then a mathematical model was developed to predict the colonization area of these species with environmental conditions. The tissue H2O2 concentration decreases with increasing temperature for E. densa and increases for other species, including native species. Therefore, native species grow intensively in spring; however, they often deteriorate in summer. For E. densa, on the other hand, H2O2 concentration decreases with high water temperature in summer, allowing intensive growth. High solar radiation increases the H2O2 concentration, deteriorating the plant. Although the H2O2 concentration of E. densa increases with low water temperature in winter, it can survive in deep water with low H2O2 concentration due to diffused solar radiation. Currently, river rehabilitation has created a deep zone in the channel, which supports the growth and spreading of E. densa.